Patrimonialiser un héritage controversé : la ville de Sabaudia dans les marais Pontins - Constance Ringon (In Situ)
This article looks into the city of Sabaudia, built between 1933-1934 during the sanitation and reorganization of the Pontine Marshes, undertaken by the fascist Italian regime in the first half of the 20th century. Here we investigate and question the criteria defining this city as a “modern” and “rationalist” heritage site, through the reconsideration of its planning and its buildings from the 1970s onward. This article considers the recent methods of conservation, preservation and restoration of this heritage site alongside the way in which certain of the city’s buildings were ignored and subjected to damnatio memoriae at the end of World War II. This article aims to understand how the attempts to take into account the Italian historical legacies were rejected in the 70s and 80s, only to be later associated with the promotion and valorization of the city since the turn of the millennium. By presenting renovation/restoration efforts, many questions arise concerning the modern aesthetic, the relationship with landscapes, the uses, the techniques and valorization efforts in a città di fondazione.